Government Internal Control System, Role and Comparison of the Committee of Sponsoring Organization (COSO) Revised Internal Control Framework - Tahang, Rahmawansyah Andi; Haliah, Haliah; Nirwana, Nirwana (Invoice : Jurnal Ilmu Akuntansi, 2023)
This study investigates the role of the Government Internal Control System and its points of difference with the revised version of the COSO internal control framework. The Government's Internal Control System is regulated in Government Regulation No. 60 of 2008 concerning the Government's Internal Control System. The Government's Internal Control System aims to provide adequate assurance for the achievement of effectiveness and efficiency in achieving the objectives of implementing State government, reliability of financial reporting, safeguarding State assets, and compliance with laws and regulations. Government Regulation No. 60 of 2008 is an adaptation of the internal control recommended by The Committee of Sponsoring Organizations (COSO) in 1992. In its development, COSO has updated the integrated framework of internal control in 2013. Seventeen principles of internal control were explicitly introduced that should be considered by the government to formulate new regulations related to the Government's Internal Control System. This study highlights the important role of internal control in the management of organizations both in the private sector and in government